Enhancing Children’s Interest in Reading through Storytelling - Lanny Hidajat (MITRA: Jurnal Pemberdayaan Masyarakat, 2017)
The purpose of this community service is to enhance the interest of young children in the elementary level to read by using storytelling. It is important to develop the love to read from early on since the mastery of reading skills has many benefits. In this community service, the committee performed storytelling to 75 third grade students at the elementary level. During the service, some data were collected to evaluate if storytelling could make the participants interested to read a given reading material. The collected data were answers to two questionnaires and a comprehension test. The results of the analysis showed that out of the 75 participants, 27 of them, actually had low interest in reading, eventually read the given reading material after watching the storytelling. In addition, all participants stated that they enjoyed the storytelling performance. These findings indicate that storytelling is potentially able to enhance the interest in reading, in particular in young children.